SOLAR COOLING SYSTEM OF A CAR - Jaalam, Nadiya (universiti teknologi petronas, 2005)
This report is based on the 'Solar Cooling System' project that has been implemented. The report will give an overview to all the processes and constructions of project work. The main objective of this project is to provide cooling in the car by using solar power. Hot day and high temperature will give uncomfortable situation to most people, especially when they get into their car after parking for several hours in open space. The person could not even hoid the steering or sit comfortably on the seat because the things are already heat up. They also feel hot when they open the window during the car moving for saving the fuel or the air conditioning is not functioning. In order to reduce the high temperature, this project will utilize the solar (photovoltaic) energy as a source to the cooling system in a car. The solar (photovoltaic) energy will charge the battery instead of activating the system. The battery will be used as a back up when solar energy is not sufficient and generates other electronic devices in the car.A thermistor that contains in control unit will be used to sense the temperature difference. When the temperature has reached to the temperature that has been set, the cooling system will turn on in order to reduce the temperature inside the carand suck the hot air out. The research and design stage will be complete during the first semester and construction stage will be done during the second semester. The analysis of cooling system to the real application will also be carried out to fulfill the design requirement instead of improving it.